2020
DOI: 10.21037/jtd.2020.03.83
|View full text |Cite
|
Sign up to set email alerts
|

The arterial-ligation-alone method for identifying the intersegmental plane during thoracoscopic anatomic segmentectomy

Abstract: Background: Currently, methods for identifying the intersegmental plane during anatomical segmentectomy can be classified into 2 categories: the bronchial method and the vascular method. One of the vascular methods, the arterial-ligation-alone method, has not yet been validated or objectively evaluated in a large case series. We thus aimed to confirm that the arterial-ligation-alone method could effectively and accurately identify the intersegmental plane. Methods: We retrospectively reviewed the records of 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…A statistically significant (p < 0.05) improvement in surgeon opinion on ease and confidence in planning was observed, with a median difference of 2 when the CT Likert scale score was subtracted from the 3D-CT Likert scale score. and statistical priors can complement existing approaches to fissure identification such as bronchial ligation (17), arterial ligation (18), and indocyanine green (ICG) (19). In future work, we plan to add this additional information to the virtual 3D models.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A statistically significant (p < 0.05) improvement in surgeon opinion on ease and confidence in planning was observed, with a median difference of 2 when the CT Likert scale score was subtracted from the 3D-CT Likert scale score. and statistical priors can complement existing approaches to fissure identification such as bronchial ligation (17), arterial ligation (18), and indocyanine green (ICG) (19). In future work, we plan to add this additional information to the virtual 3D models.…”
Section: Resultsmentioning
confidence: 99%
“…Various computational techniques exist on how to estimate the inter-segmental fissure when it cannot be directly observed in the CT scan ( 13 , 16 ). Virtual 3D models with segmental surfaces derived from medical scans and statistical priors can complement existing approaches to fissure identification such as bronchial ligation ( 17 ), arterial ligation ( 18 ), and indocyanine green (ICG) ( 19 ). In future work, we plan to add this additional information to the virtual 3D models.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 The automatic approach has only achieved an overall detection sensitivity of 77% compared with the manual approach and is not satisfactory in the clinical setting. 12 In addition, Fu et al 32 reported that the intersegmental planes are inaccurate when using this method because of the presence of pores of Kohn, canals of Lambert, and direct airway anastomosis. Although Fu et al 32 confirmed that arterial ligation alone allowed for identification of the intersegmental planes in 99 (95.2%) patients during thoracoscopic anatomical segmentectomy, they could not accurately identify the intersegmental plane and the spatial location of the mass in a pulmonary segment before the surgical operation to shorten the surgical time.…”
Section: Discussionmentioning
confidence: 99%
“…12 In addition, Fu et al 32 reported that the intersegmental planes are inaccurate when using this method because of the presence of pores of Kohn, canals of Lambert, and direct airway anastomosis. Although Fu et al 32 confirmed that arterial ligation alone allowed for identification of the intersegmental planes in 99 (95.2%) patients during thoracoscopic anatomical segmentectomy, they could not accurately identify the intersegmental plane and the spatial location of the mass in a pulmonary segment before the surgical operation to shorten the surgical time. Therefore, we have herein proposed a novel and effective way to segment the lung into arteriopulmonary segments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation